Haiti : 2007 Article IV Consultation, First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Nonobservance and Modification of Performance Criteria; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that the transitional government that took over in Haiti following President Aristide's departure in February 2004 implemented prudent fiscal and monetary policies, and significantly improved governance and transparency in public sector operations. These efforts were supported by an IMF staff-monitored program and two successive arrangements under the Emergency Post Conflict Assistance (EPCA) facility between mid-2004 and late-2006. Executive Directors viewed that the key challenge in future will be to consolidate stabilization gains while establishing higher, sustained growth.